The extent and some of the vicissitudes of psychological traumatisation at the hands of violent crime in first year university students - Jacobs, Franchelle Pauline (My University, 2002)
A review of the relevant South African trauma literature indicated that very little research into the effects of direct and indirect violent crime exposure has been undertaken. The present study examined some of the psychological sequelae given extremely high levels of violent crime exposure in South Africa (Nedbank ISS Crime Index, 2001 ). This study focused on violent crime in Gauteng, South Africa, as experienced by a sample of 1st year University of the Witwatersrand students. The sample (n = 367) consisted of 1 st year Bachelor of Arts, Bachelor of Science and Bachelor of Commerce students. A quantitative research methodology was used, in which levels of trauma were assessed by using the Impact of Event Scale (Horowitz et al., 1979). The Dimensions of Trauma Scale (Esprey, 1996) and the Direct and Indirect Exposure to Violent Crime Scales, constructed by the researcher, were used to measure violent crime exposure. The current research adopted an epidemiological lens and focused on the prevalence of both direct and indirect traumatic exposure to violent crime, in a sample of 1 st year South African university students in Gauteng, and the prevalence of any resultant traumatic stress symptomatology. The results of the research yielded high levels of direct and indirect exposure to violent crime. Thirty-five percent of the students reported direct exposure to violent crime and 62 % reported indirect exposure to violent crime. Multiple exposure to trauma was evident in the current study's sample. It was found that 19% of the sample reported substantial levels of PTSD symptomatology on the Impact of Event Scale (Horowitz et al., 1979). 4 A further focus of the current study included an examination of the relationship between the nature of the traumatogenic event (i.e. the nature, severity and subjective perception of the stressor), the posttrauma environment (i.e. counselling, social support and previous exposure to trauma) and personal factors (i.e. demographics, health status, substance abuse, psychiatric and family psychiatric history and a sense of coherence) and both traumatic exposure to violent crime and traumatic symptomatology. The results of the study yielded many statistically significant relationships and statistically significant effects between the factors chosen as part of the relational aspect of the current study. Statistically significant results were found with regards to the nature of the traumatogenic event (e.g. mugging, attempted sexual assault), features of the posttrauma environment (e.g. social support, previous trauma exposure) and personal factors ( e.g. demographics, substance use) in relation to both direct and indirect traumatic exposure to violent crime and traumatic symptomatology. The results of the relational aspect of the current study suggest that many factors are implicated with regards to traumatic exposure and traumatic stress manifestations, highlighting and adding to continuing debates regarding the complex and multifaceted nature of the study of trauma. Finally, the study examined whether there was a relationship between traumatic exposure and traumatic symptomatology. The results of the study found statistically significant relationships between traumatic exposure, in this case, violent crime, and traumatic symptomatology. This result contributes to the body of traumatic stress literature regarding the relationship between the nature of the stressor and traumatic symptomatology. 5 The study added to current knowledge in the field of traumatic stress generally, and more specifically expanded on the effects of criminal violence in South Africa. The study also illustrated the importance of acknowledging the effects of indirect exposure to violent crime. A further, fairly novel contribution of the current study regards the examination of variables in relation to traumatic exposure. Finally, a number of suggestions for future research are discussed.
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Master of Arts (Psychology)
Keywords: Post-traumatic stress disorder; Violence--South Africa--Psychological aspects